Forging a Consensus : Historical Essays on Toronto - Russell, Victor Loring (Book collections on Project MUSE., 1984)
In this collection of essays, published to mark the sesquicentennial, a number of historians, geographers, and political scientists analyse the history of the relationship between the corporation of the city of Toronto and the city that it administers.